Discrimination of infested cotton squares by females of Anthonomus grandis - Nussenbaum, Ana Laura; Devescovi, Francisco; Fogar, Mariela Noemi; Almada, Melina Soledad; Salerno, Juan Carlos; Cladera, Jorge Luis; Lecuona, Roberto Eduardo; Segura, Diego Fernando (2017)
The avoidance of infested squares of Gossypium hirsutum as oviposition substrate by females of Anthonomus grandis was studied following two approaches. First, the preference for oviposition in infested versus non-infested squares was studied in laboratory. Second, the distribution of ovipositions by A. grandis in nature was analyzed in cotton plots from Argentina. In addition, the consequences of multiple ovipositions were assessed in terms of emergence rate, adult weight and sex ratio. In the laboratory, the number of ovipositions was significantly higher in non-infested than in infested squares. Likewise, females were found to reject infested squares more frequently than non-infested squares. In the field, oviposition pattern fitted a uniform distribution for squares collected from the ground, while the distribution in squares sampled from the plant fitted random and uniform distributions. This suggests that oviposition decisions could be dynamic and change with the infestation conditions. Multiple ovipositions resulted in the elimination of competing larvae between L1 and L2 instars. The weight of the individual that develops to the adult stage was negatively affected by the level of larval competition, and the sex ratio deviated toward females. Our results suggest that females of A. grandis tend to avoid already infested squares. This behavior would allow reducing the levels of intraspecific competition, which we also found can seriously affect the development of their progeny. A deeper knowledge of the oviposition behavior of A. grandis could contribute to developing control methods against this important cotton pest